The Association Between The Gly972Arg Polymorphism in IRS1 Gene and The Risk of Prediabetes Amongst Vietnamese Women - Nguyen, Thi Trung Thu (H. : ĐHQGHN, 2019)
Insulin receptor substrate 1 (IRS1) is a ligand of the insulin receptor tyrosine kinase and participates in the insulin receptor signal transduction pathway. Dysregulations in IRS1 expression and function increase incidence of insulin-resistant states such as prediabetes and type 2 diabetes. The study was aimed at investigating the association of the Gly972Arg (rs1801278) polymorphism in IRS1 gene with prediabetes in Northern Vietnamese women. The case-control study consisted of 1617 women (250 prediabetic cases and 1367 normoglycemic controls). The IRS1 Gly972Arg polymorphism was genotyped in these subjects using polymerase chain reaction–restriction fragment length polymorphism. The frequency of the „„A‟‟ allele of the Gly972Arg (G>A) polymorphism was similar between the normal glucose and prediabetic subjects (2.7% and 2.6%, respectively). There was no significant difference in the genotypic frequency between the control and prediabetic cases (P = 0.673). The IRS1 ly972Arg polymorphism was not associated with the risk of prediabetes in Vietnamese women before and after adjusted for socio-economic, lifestyles and clinical factors (P > 0.05)